Empowerment of the Fisherman Community Based on Local Wisdom in the Administration District of a Kepulauan Seribu DKI Jakarta Province - Purnomo, Purnomo; Daraba, Dahyar; Achmad, Mansur; Tahir, Irwan (Budapest International Research and Critics University, 2021)
This study aims to find a new model of community empowerment based on local wisdom, natural capital and accelerated social capital with the duties and functions of district officials in providing public services, both formally and in terms of providing facilities and infrastructure (public goods), using qualitative descriptive methods. The information is determined by purposive sampling technique for competent parties to provide accurate information related to the problem. While the snowball technique is used on the policy object that has an impact. Interviews, Observations and Literature Studies are the techniques used in collecting data. Meanwhile, data reduction, data presentation and conclusion drawing are qualitative data analysis techniques used in this study. The results of this study are it depicts the Empowerment of the Fisherman Community of the Kepulauan Seribu, Social Capital and Natural Capital to accelerate with easy access to public services and public goods to improve the quality of life and competitiveness. Regulating the use of natural resources with coral reef and mangrove ecosystems through zoning, so that they can manage tourism objects with different characteristics. Cultivating New Livelihoods due to the growing development of the fisheries, tourism, transportation, micro-trade businesses, services, and other employment opportunities along with the activities in the Kepulauan Seribu.